Life Writings, Autobiographical Subjects: Exploring Colonial Narratives and Anti-Memory in African Freedom Fighters' Texts. Issue 2 (17th February 2022) - Adeniyi, Emmanuel
ABSTRACT: This article attempts to give voice to freedom fighters who died during the struggle for independence in Africa. Due to their untimely deaths, they could not self-narrate their encounters with colonial subjectivity. Taking cues from Patrice Lumumba and Steve Biko, it argues that the unlikely documents of these nationalists can be (re)constructed as autobiographies by reawakening their muted self and deploying them as anti-memory to de-centre colonial grand narratives. Through Howarth's autobiographical elements, Ngugi's history typologies, and postcolonial autobiography, the article contends that the absence of autobiographies of some African nationalists creates gaps in anti-colonial historical memory and African freedom fighting literature. It affirms the significance of updating the colonial archive, considering the exclusion of overriding historical contingencies from its memory. The article also asserts the importance of constructing self-narratives for African social activists and using the narratives as countervailing texts against dominant univocal narratives in colonial archival memory.